Relationship between alcohol outcome expectancies, self-efficacy, motives and alcohol consumption among university students - Baltrušaitytė, R.; Bulotaitė, L. (Psichologija, 2011)
Alcohol use is widespread among university students. While searching for the factors associated with drinking, scientists more often acknowledge the importance of various cognitive-motivational variables. It is recommended to consider these variables when developing effective prevention and intervention programs. The cognitive-motivational variables examined in this study were: alcohol outcome expectancies, drinking motives, motives for not drinking, and drinking refusal self-efficacy. The purpose of the study was to examine the relationship between alcohol outcome expectancies, motives, self-efficacy and alcohol consumption among Lithuanian university students. Another aim was to propose and test a meditational model in which alcohol consumption and alcohol-related problems are predicted by expectancies, motives and self-efficacy. 308 students from five Lithuanian universities participated in this study. All participants completed the Drinking Expectancy Questionnaire – revised (DEQ-r), Drinking Refusal Self-efficacy Questionnaire – revised (DRSEQ-r), Drinking Motives Questionnaire (DMQ), motives for not drinking questionnaire and one more questionnaire assessing drinking patterns and alcohol-related problems. The results have shown that the male gender, stronger motives to drink and a weaker drinking refusal self-efficacy predict a larger quantity of alcohol consumed per occasion. More frequent drinking was also predicted by an earlier age of drinking onset. A larger number of alcohol-related problems was predicted not only by the frequency and quantity of alcohol consumption, but also by stronger motives to drink and a weaker drinking refusal self-efficacy. The relationship between positive alcohol outcome expectancies and alcohol consumption was mediated by motives and drinking refusal self-efficacy. Motives to drink predict alcohol consumption and alcohol-related problems directly and indirectly – through self-efficacy. Drinking refusal self-efficacy predicted alcohol consumption directly, and the relationship between self-efficacy and alcohol-related problems was mediated by alcohol consumption. Strong positive alcohol outcome expectancies and drinking motives may be considered as potential risk factors for heavy drinking and alcohol-related problems. Strong drinking refusal self-efficacy and strong motives for not drinking because of indifference toward alcohol may be considered as protective factors against drinking and alcohol-related problems among university students.
Keywords: alcohol consumption; expectancies; motives; self-efficacy